Pooled long-term outcomes from two randomized trials of axillary node sampling with axillary radiotherapy versus axillary node clearance in patients with operable node-positive breast cancer. Issue 1 (15th December 2015) - Bing, A U; Kerr, G R; Jack, W; Chetty, U; Williams, L J; Rodger, A; Dixon, J M
Abstract: Background: The aim was to determine long-term overall, breast cancer-specific and metastasis-free survival as well as axillary relapse rate from a pooled analysis of two randomized trials in women with operable breast cancer. These trials compared axillary node sampling (ANS), combined with axillary radiotherapy (AXRT) if the sampled nodes were involved, with axillary node clearance (ANC). Methods: Data from two clinical trials at the Edinburgh Breast Unit that randomized patients between 1980 and 1995 were pooled. Long-term survival was analysed using Kaplan–Meier curves and Cox regression, with separate analyses for patients with node-positive (ANS + AXRT versus ANC) and node-negative (ANS versus ANC) disease. Results: Of 855 women randomized, 799 were included in the present analysis after a median follow-up of 19·4 years. Some 301 patients (37·7 per cent) had node-positive disease. There was no evidence of a breast cancer survival advantage for ANS versus ANC in patients with node-negative disease (hazard ratio (HR) 0·88, 95 per cent c.i. 0·58 to 1·34; P = 0·557), or for ANS + AXRT versus ANC in those with node-positive breast cancer (HR 1·07, 0·77 to 1·50; P = 0·688). There was no metastasis-free survival advantage for ANS versus ANC in patients with node-negative tumours (HR 1·03, 0·70 to 1·51; P = 0·877), or ANS + AXRT versus ANC in those with node-positive disease (HR 1·03, 0·75 to 1·43; P = 0·847). Node-negative patients who underwent ANS had a higher risk of axillary recurrence than those who had ANC (HR 3·53, 1·29 to 9·63; P = 0·014). Similarly, among women with node-positive tumours, the risk of axillary recurrence was greater after ANS + AXRT than ANC (HR 2·64, 1·00 to 6·95; P = 0·049). Conclusion: Despite a higher rate of axillary recurrence with ANS combined with radiotherapy to the axilla, ANC did not improve overall, breast cancer-specific or metastasis-free survival. Axillary recurrence is thus not a satisfactory endpoint when comparing axillary treatments. Abstract : No difference in outcome